Kinerja Badan Akreditasi Nasional Perguruan Tinggi (BAN-PT); Relevansinya dengan Fungsi Pembinaan Peningkatan Kualitas Program Studi - Nasrun, M. (Universitas Tanjungpura, 2009)
This research aims at describing the performance of the BAN-PT (The National Accreditation Board for Higher Education) in line with its function to guide the imporvement of the study program quality in the six focuses as follows: (1) the potency of criteria as an evaluation standard; (2) potency of choosing and applying techniques and tools; (3) potency of process stages in accommodating the need for data to measure quality and the relavance of study program (filling borang workshop I, visitation, and workshop II); (4) appli-cation of the evaluation criteria; (5) achievement of the target of study program and (6) improvement of quality of the accredited study program quantitatively. Keyword: performance of the BAN-PT, relevance, guidance and quality